The Role of Principal Leadership in Preparing Guidance and Counseling to Face Generation Z - Reni Silviah (Siber International Journal of Sport Education, 2024)
The Role of Principal Leadership, Guidance and Counseling, to Face Generation Z. The aim is to analyze whether the principal's leadership in preparing guidance and counseling plays a role in Generation Z. The method of writing this scientific article is by using the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other online media. The results of this study are:1) Principal's leadership plays a role in Generation Z, 2) Guidance and Counseling plays a role in Generation Z, 3) Principal's leadership plays a role in preparing guidance and counseling to face Generation Z. Apart from these 2 exogenous variables that influence the endogenous variable of Generation Z, there are many other factors including motivation, environment, and organizational culture.